2012
DOI: 10.1200/jco.2011.36.2517
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Randomized Controlled Trial of Individual Meaning-Centered Psychotherapy for Patients With Advanced Cancer

Abstract: Purpose Spiritual well-being and sense of meaning are important concerns for clinicians who care for patients with cancer. We developed Individual Meaning-Centered Psychotherapy (IMCP) to address the need for brief interventions targeting spiritual well-being and meaning for patients with advanced cancer. Patients and Methods Patients with stage III or IV cancer (N = 120) were randomly assigned to seven sessions of either IMCP or therapeutic massage (TM). Patients were assessed before and after completing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
350
1
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 330 publications
(370 citation statements)
references
References 25 publications
8
350
1
11
Order By: Relevance
“…Additionally, a study that examined gene transcriptional profiles found that eudaimonic well-being (an overarching umbrella term that includes purpose) was associated with enhanced expression of antiviral response genes and reduced expression of proinflammatory genes (31). Furthermore, and perhaps most importantly, purpose-along with other components of psychological well-being-have become the focus of multiple intervention studies designed to improve a person's life outlook (10,(32)(33)(34)(35). Therefore, it may provide a point of intervention for improving health outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study that examined gene transcriptional profiles found that eudaimonic well-being (an overarching umbrella term that includes purpose) was associated with enhanced expression of antiviral response genes and reduced expression of proinflammatory genes (31). Furthermore, and perhaps most importantly, purpose-along with other components of psychological well-being-have become the focus of multiple intervention studies designed to improve a person's life outlook (10,(32)(33)(34)(35). Therefore, it may provide a point of intervention for improving health outcomes.…”
mentioning
confidence: 99%
“…The technique is typically used after standard care (e.g., cognitive behavioral therapy and pharmacotherapy) and is known to help prevent relapse. Additionally, early randomized controlled trials have shown that a meaning-centered therapy, delivered either in a group or individual format, can help raise meaning and purpose in life among people with cancer (32,33). Finally, as people retire, several volunteering programs have emerged that help older adults transition into meaningful and socially engaging activities, likely enhancing their sense of purpose in life (e.g., Experience Corp, Retired and Senior Volunteer Program, Foster Grandparents) (52).…”
mentioning
confidence: 99%
“…Meaning-centered psychotherapy, a brief (seven-session) intervention offered to critically ill patients that aims to increase a sense of meaning and decrease emotional distress [16], has been shown to benefit cancer patients [16,17]. We know of no comparable randomized studies of psychodynamic psychotherapy in the cancer setting.…”
Section: Manualized Therapy Versus Psychodynamic Therapy: a Case Studymentioning
confidence: 99%
“…Cada sesión aborda un tema específico: introducción al concepto del sentido (1), cáncer y sentido (2), historia del concepto de sentido (3)(4), fuentes del sentido (5-7), y cierre (8) (Cuadro 1).…”
Section: Descripción De La Intervenciónunclassified
“…Por ello, requieren de un modelo de intervención ajustado a sus necesidades. El modelo de psicoterapia desarrollado por William Breitbart (4) ha demostrado su eficacia en este grupo de pacientes con cáncer avanzado.…”
Section: Introductionunclassified